2019
DOI: 10.1177/1756286419846058
|View full text |Cite
|
Sign up to set email alerts
|

Neurochemical markers in CSF of adolescent and adult SMA patients undergoing nusinersen treatment

Abstract: Background: There is limited information on neurochemical markers being used to support and monitor the affection of motoneurons in patients with spinal muscular atrophy (SMA). The objective of this study was to examine neurochemical markers in cerebrospinal fluid (CSF) under treatment with the antisense-oligonucleotide (ASO), nusinersen. Methods: We measured markers of axonal degeneration [neurofilament light chain (NfL) and phosphorylated neurofilament heavy chain (pNfH)] along with basic CSF parameters in 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
42
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 52 publications
(53 citation statements)
references
References 28 publications
9
42
0
2
Order By: Relevance
“…Total protein concentrations were increased (0.441 vs. 0.372 g/L; p < .01) in the SMA patient group after 10 months of nusinersen treatment compared with the pre‐treatment condition (Table ; Figure S1a). There was also a trend toward an increased Q alb after nusinersen treatment as reported recently (Wurster, Günther, et al, ). However, this increase did not reach the level of significance in our patient cohort ( p = .07).…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…Total protein concentrations were increased (0.441 vs. 0.372 g/L; p < .01) in the SMA patient group after 10 months of nusinersen treatment compared with the pre‐treatment condition (Table ; Figure S1a). There was also a trend toward an increased Q alb after nusinersen treatment as reported recently (Wurster, Günther, et al, ). However, this increase did not reach the level of significance in our patient cohort ( p = .07).…”
Section: Resultssupporting
confidence: 84%
“…Plasma pNfH was recently described as a potential marker of disease activity and treatment response in infants with SMA 1 (Darras, Crawford, et al, ). In contrast, another recent study provided evidence that CSF concentrations of neurofilament light chain (NfL) and pNfH are neither elevated in adolescent or adult SMA 2 and SMA 3 patients compared with controls nor influenced by the loading dosing of nusinersen (treatment day 63) (Wurster, Günther, et al, ). Hence, the authors of the latter work concluded that CSF neurofilament concentrations would not be useful as diagnostic or monitoring markers in adolescent/adult SMA 2 or 3 (Wurster, Günther, et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Overall, the selection of these biomarkers is based on the results of previous studies with neurodegenerative diseases. pNfH has been shown to be a reliable marker in motor neuron diseases, such as amyotrophic lateral sclerosis and SMA type 1 and 2 [15], but not in adult SMA3 [17]. The elevation of pNfH indicates an axonal loss and a correlation between neurofilament level and disease progression is suspected [15,18].…”
Section: Laboratory Testingmentioning
confidence: 99%
“…That brought the idea of using antisense oligonucleotide, which blocks the intronic splicing silencer binding site at exon 7, leading to an increase in SMN protein levels in motor neurons (Figure c and d) (Bennett, Baker, Pham, Swayze, & Geary, ; Wurster & Ludolph, ). This particular 18 nucleotides long antisense oligonucleotide is called nusinersen that has been approved by the Federal Drugs Administration as well as European Medicines Agency as the disease modifying treatment for SMA and commercially available as “Spinraza.” However, because of the inability to cross blood‒brain barrier, nusinersen is administered intrathecally in patients (Stolte et al, ; Wurster, Gunther, et al, ). Long‐term treatment of nusinersen is found to alleviate SMA disease symptoms and improve lifestyle in patients suffering from SMA1 and SMA2.…”
Section: Therapy For Smamentioning
confidence: 99%